2013
DOI: 10.1016/j.rbmo.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Does supplementation of in-vitro culture medium with melatonin improve IVF outcome in PCOS?

Abstract: Human pre-ovulatory follicular fluid (FF) contains a higher concentration of melatonin than serum. The aim of this study was to evaluate the effect of melatonin supplementation of culture medium on the clinical outcomes of an in-vitro maturation (IVM) IVF-embryo transfer programme for patients with polycystic ovarian syndrome (PCOS). Melatonin concentrations in the culture media of granulosa cells (GC) or cumulus-oocyte-complexes (COC) were measured and the clinical outcomes after using IVM media with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 32 publications
7
68
0
3
Order By: Relevance
“…Conversely, of 59 women not given supplemental melatonin fertility was not changed (relative to the previous cycle). In a more recent study, Kim and co-workers [59] reported that the incubation of ova from infertile women with polycystic ovarian syndrome in a melatonincontaining solution also improved the implantation and pregnancy rates during IFV-ET. For several reasons, the outcome of these studies has important implications and should encourage further tests on the usefulness of melatonin to overcome infertility and improve IVF-ET outcome.…”
Section: Melatonin: Utility In Ivf-et and In Infertilitymentioning
confidence: 98%
“…Conversely, of 59 women not given supplemental melatonin fertility was not changed (relative to the previous cycle). In a more recent study, Kim and co-workers [59] reported that the incubation of ova from infertile women with polycystic ovarian syndrome in a melatonincontaining solution also improved the implantation and pregnancy rates during IFV-ET. For several reasons, the outcome of these studies has important implications and should encourage further tests on the usefulness of melatonin to overcome infertility and improve IVF-ET outcome.…”
Section: Melatonin: Utility In Ivf-et and In Infertilitymentioning
confidence: 98%
“…[104] Deer Animal Subcutaneous implantation of 40 mg Elevates the serum FSH and LH levels, increases number of corpora luteal and the number of embryos [105] Human Oocytes 10 µmol/L during in vitro maturation Increases the preimplantation and pregnancy rate [106] Sheep Animal Subcutaneous implantation of 40 or 80 mg Increases corpus luteal, the number of recovered embryos, the pregnancy and birth rates, and the lambs born per embryo [107] Porcine Donor cell and embryos 10 -10 M in the medium for donor cell and 10 -9 M during in vitro culture of embryos produced by SCNT Increases the proliferation of fetal fibroblasts, blastocysts rate, reduces the apoptotic nuclei. Also, it upregulates BCL2L1 and downregulates BAX and p53.…”
Section: Melatoninmentioning
confidence: 99%
“…In the Fertility Center of the CHA Gangnam Medical Center, hCG priming has been significantly more successful than no priming for implantation (26.4% vs. 22.6%) and for the pregnancy rate (61.9% vs. 45.7%) [23]. Determining the optimal timing for oocyte collection is the most significant dilemma for IVM.…”
Section: Clinical Regimens In Ivmmentioning
confidence: 99%